Hydroamination of unactivated alkenes catalyzed by novel platinum(II) N-Heterocyclic carbene complexes - Cao, Peng; Cabrera, José; Padilla, Robin; Serra, Daniel; Serra, Daniel; Rominger, Frank; Limbach, Michael (Organometallics, 2012)
Cationic platinum(II) complexes with bi- or tridentate (pincer) functionalized NHC ligands were found to be catalytically active in the hydroamination of unactivated alkenes. In some cases, the presence of water had an activating effect on the complexes. Reactions with the N-nucleophilic substrate morpholine led to a noncatalytic reaction in which the deprotonation product of the key cationic β-aminoalkyl platinum complex could be isolated and characterized. Surprisingly, attempted protonation of this complex did not give the expected N-alkylated product, indicating either the thermodynamic unfavorability of C-Pt bond cleavage or its kinetic inertness.
Gesehen am 17.04.2018